Bioenergy for sustainable development in Africa - Rutz, Dominik; Janssen, Rainer (Springer Netherlands, 2012)
This contribution to the current global discussion about the sustainability of bioenergy addresses the fact that this debate often ignores the needs and opinions of developing countries. The book specifically addresses bioenergy development opportunities and associated risks for Africa.   The contributions to the work relate the experiences of selected authors from Africa, Europe and other continents and include material from researchers, investors, policy makers and other stakeholders, such as representatives of NGOs. Readers will, then, find a multitude of perspectives on the issue, going well beyond the academic field.   The work builds on the results of the COMPETE Bioenergy Competence Platform for Africa, which was supported by the European Commission and coordinated by WIP Renewable Energies, Germany. The five sections cover biomass production and use, biomass technologies and markets in Africa, biomass policies, sustainability, and financial and socio-economic issues. This valuable work is, in effect, a single-source treatment of a key energy sector in a part of the world which still has a lot of unrealised potential for development.